Hak Istri untuk Menolak Dipoligami: Musyawarah dalam Rumah Tangga Perspektif Al-Baqarah (2): 233 - Nasrullah Ainul Yaqin (Indonesian Journal of Shariah and Justice, 2022)
The Universal Declaration of Human Rights (UDHR) equalizes male and female position includes of marriage life as it is mentioned in subsection 16 (1). That subsection is also taken by the Government of Indonesia as thebase of Law No. 23 2004 which contains of the Domestic Violence Abolishment (UU KDRT) to protect the women (wife) from the violences (phisically, psychologically, and sexually) which is committed by men (husbands). While in Islam both Sunnis and Syi’i scholars permit the polygamy according to an-Nisâ’ (4): 3. Wahbah az-Zuḥailî argued that the husband is legalized doing polygamy by two conditions, they are: the fairness and ability of providing for wifes by the husband. These two conditions absolutely closes the wife’s right to reject the polygamy. Though the reality are found many wifes are hurted psychologically caused by husbands who practice the polygamy. Therefore, this article discusses specifically the content of al-Baqarah (2): 233 and its implications for the wife's right to reject the polygamy. The verse “fa in arâdâ fiṣâlan ‘an tarâḍin minhumâ wa tasyâwurin fa lâ junâḥa ‘alaihimâ” is not only turns out the weaning matter, but also to other matters in the household, including polygamy. In other words, deliberations and mutual relationships between husband and wife is not limited by the issue of weaning children only, but also concerning other issues such as polygamy, where in the deliberations the wife has the right to accept or reject the wishes of her husband to do polygamy.